Characterization and modification of castor oil extracted from the newly malaysian produced castor beans - Wan Aliuddin, Wan Razdi (2012)
Vegetable oils, either edible or non-edible, are widely used in huge number of applications in industry. Ricinus communis (castor plant) is one of the non-edible vegetable oil and its usage in many industries as a raw material and additives is rapidly growing. In this research, the Malaysian newly produces castor beans are extracted and the castor oil is characterized. The castor oil that is obtained from extraction is refined and modified for further uses. The extraction process involve four steps which are clearing, drying, winnowing and also grinding to get high yield of oil. The castor cake then extracted using the soxhlet extractor and hexane as the solvent. The extracted castor oil produced is characterize by determining the acid value, saponification value, iodine value, specific gravity, viscosity of the oil, the refractive index, and pH value. The crude oil from the extraction process then refines by degumming and neutralization process and then the neutralize oil is bleached. The Malaysian castor oil properties are compared with the ASTM standard specifications. The conclusion is the properties of Malaysian crude and refined castor oil is determined and be compared with the world standard specification of castor oil. The refined castor oil then modified for further uses. The different castor seed from different area which is Casa 5 and Casa 101 is extracted to obtain the castor oil and identify which location in Malaysia that the castor seed produces more oil content and have the same standard with world castor oil quality.